Do fiscal rules matter? A survey on recent evidence - Thomas Brändle; Marc Elsener (University of Basel, Center of Business and Economics (WWZ), 2023)
Fiscal rules are argued to be important for sound and sustainable fiscal policies and have been increasingly adopted over the last 20 years. However, as increased fiscal pressure and fiscal risks urge countries to address the public debt legacy left by recent economic crises, fiscal rules come under greater scrutiny. To inform the debate on fiscal frameworks, this paper presents a comprehensive survey of the empirical literature on the impact of fiscal rules. In particular, we discuss the recent empirical literature that investigates the impact of fiscal rules on various elements related to fiscal performance and beyond. Our survey finds that fiscal rules are associated with improved fiscal performance as approximated by improved budget balances, lower debt and lower public spending volatility. Furthermore, empirical research finds that fiscal rules are related to more accurate budget forecasts and improved sovereign bond ratings. From a macroeconomic perspective, well-designed fiscal rules do not principally undermine public investment and do not increase pro-cyclicality in fiscal-policy making. These results, however, also depend on the broader economic and institutional context. Moreover, there is emerging literature that links fiscal rules to broader outcomes, such as income distribution and political polarisation. We discuss methodological challenges related to identification and point to avenues for future research.
Keywords: E61; E62; H1; H6; 330; Fiscal rules; independent fiscal institutions; public debt; fiscal policy; fiscal sustainability